The Beacon Wiki: Mapping oncological information across the European Union - Veronica Coppini; Giulia Ferraris; Maria Vittoria Ferrari; Dario Monzani; Margherita Dahò; Elisa Fragale; Roberto Grasso; Ricardo Pietrobon; Aline Machiavelli; Lucas Teixeira; Victor Galvão; Gabriella Pravettoni (BMC Medical Informatics and Decision Making)
Abstract Background Accessing comprehensive oncological data is essential for efficient and quality healthcare delivery and research. However, obstacles, such as data fragmentation and privacy concerns which may hold back progress in this area, exist. The Cancer Care Beacon project addresses these barriers consolidating oncological information across the 27 member states of the European Union (EU) with the goal of creating a Beacon wiki free data online repository. Methods The Cancer Care Beacon project involves thorough data collection from various sources, including hospital websites, PubMed, ClinicalTrials.gov, and national health institutions. The main focus of metadata retrieval is placed on descriptive details about data sources, thus warranting compliance with privacy regulations and ethical standards. In addition, manual examination and semi-automated methods are included in the process, enabling a registry of administrative databases, cancer registries, and other relevant databases. Results Project findings demonstrate the success in the realisation of a comprehensive repository of oncological data sources across the EU assisting informed decision-making regarding the selection and utilisation of resources. Still, challenges such as limited accessibility and low engagement from database providers persist. Conclusion The Beacon Wiki represents a significant step in addressing disparities in oncological data access and advancing cancer care and research in Europe. By providing comprehensive metadata on cancer-related data sources, Beacon Wiki empowers stakeholders and promotes collaboration in cancer care and research. Continuous efforts are needed to enhance data accessibility and engagement from database providers, ultimately improving data-driven decision-making and patient outcomes in the EU. Graphical Abstract